Primary myxoid melanoma with dermoscopic findings - Tugba Kevser Ustunbas Uzuncakmak; İlkin Zindanci; Ebru I. Zemheri; Ayşe S. Karadag; Burce C. Kuru; Necmettin Akdeniz (Mattioli1885, 2017)
Myxoid melanoma is a rare variant of melanoma, which is characterized by atypical spindle cells and dense mucin deposition in dermis. This tumor is usually seen in elderly people with a similar progress in other variants of melanoma. A 28-year-old male presented to our outpatient clinic with a 6-month history of a slowly growing asymptomatic pink lesion on his arm. Dermoscopic examination revealed pink-white cristalline structures and blue-grayish ovoid globules. The lesion was totally excised with initial diagnosis of basosquamous carcinoma, amelanotic melanoma and basal cell carcinoma. Histopathological examination was consistent with myxoid melanoma. We present this case due to the rarity of myxoid melanoma and occurence in such a young age.